Determination of Morphine in Urine by HPLC Using Ion-Pair Extraction - Zou, Deqing; Zou, Yan; Yang, Yaling (Asian Journal of Chemistry, 2012)
A new method was developed for the analysis of morphine in human urine by high performance liquid chromatography (HPLC) using ion-pair extraction. By adding a kind of hyamine in organic phase, simultaneous extraction and enrichment of morphine were achieved. Effects of the types of organic solvents and carriers, the concentration of carrier and organic, the pH, the stirring rate and the extraction time on the recovery factor of analytes were investigated. Under the optimal experimental conditions, the linear detection ranges were 0.1-10 mg L-1 for the studied drugs. The limits of detection at signal-to-noise ratio of 3 were 0.03 mg L-1 for morphine. The relative recoveries ranged over 85.5-92.1 %, y = 31.276x - 8.7618, R2 = 0.9969, the relative standard deviations were 0.3-4.4 % (n = 5). This method was successfully applied to analysis of morphine in real urine specimens, revealing that the determination of morphine in urine was feasible.